The Prospects of a Unified Theory of Organizations - Helmer, Olaf (Management Science, 1958)
Despite the success of numerous sporadic efforts in the study of organizations, there is at present no unified theory of organizations. This would require a clearcut conceptual apparatus and a methodology for prediction. To achieve the former within the foreseeable future it might be wise to tie into the existing terminology of game theory; the latter may require taking a new look at the psychological problems involved and introducing something like an operations research approach to them.